L'apprendimento in età adulta: visioni storiche e prospettive teoriche - Claudia Secci (Firenze University Press, 2013)
An historical path is followed, aimed at identifying the notion of adult learning and its evolution from the ancient times until nowadays. With especial reference to the contemporary age, the concept of learning is considered in relation to the notions of education, lifelong construction of the subject, comprehension and development, as it appears in some philosophical, pedagogical and psychological perspectives. Particular attention is moreover pinned on the contribution of humanistic psychology and of andragogy.